La place de l’editor dans la procession des jeux - Antoine Gailliot (Cahiers Mondes Anciens)
In Rome, a grand procession was held before public games, where Gods and men marched from the Capitol to the Great Circus. Scholars have stressed the fundamental role of the editor, the roman magistrate in charge of the ceremony, dressed remarkably like a triumphing general, and surrounded by his friends, clients and colleagues. A faulty reading of Dionysius of Halicarnassus has led to surmise that the editor led the marching order. Using the Severian acta of the Saecular Games, combined with a careful re-reading of Dionysius, this article proposes to locate the editor behind the youths, athletes, dancers, musicians and sacrificial victims, just before the statues of the gods. Understanding the correct organisation of the pompa circensis allows in turn for a better understanding of the ritual and political stakes of the ceremony.